Hemotransfusion and mechanical ventilation time are associated with intra-hospital mortality in patients with traumatic brain injury admitted to intensive care unit - Almeida, Kelson James; Rodrigues, Ânderson Batista; Lemos, Luiz Euripedes Almondes Santana; Oliveira, Marconi Cosme Soares de, Filho; Gandara, Brisa Fideles; Lopes, Raissa da Rocha; Modesto, Daniel Rocha e Silva; Rego, Irizon Klecio Pereira (Arquivos de Neuro-Psiquiatria, 2016)
Objective To identify the factors associated with the intra-hospital mortality in patients with traumatic brain injury (TBI) admitted to intensive care unit (ICU).Methods The sample included patients with TBI admitted to the ICU consecutively in a period of one year. It was defined as variables the epidemiological characteristics, factors associated with trauma and variables arising from clinical management in the ICU.Results The sample included 87 TBI patients with a mean age of 28.93 ± 12.72 years, predominantly male (88.5%). The intra-hospital mortality rate was of 33.33%. The initial univariate analysis showed a significant correlation of intra-hospital death and the following variables: the reported use of alcohol (p = 0.016), hemotransfusion during hospitalization (p = 0.036), and mechanical ventilation time (p = 0.002).Conclusion After multivariate analysis, the factors associated with intra-hospital mortality in TBI patients admitted to the intensive care unit were the administration of hemocomponents and mechanical ventilation time.
Keywords: craniocerebral trauma; intensive care units; hemotherapy service; ventilator weaning